(untitled) (Law and world, 2019)
The important and organic part of the development of Western Civilization is deep understanding of the essence of a fair and impartial state. What does a fair impartial state mean, what are its fundamental principles built upon, what elements does it imply in itself? These issues have always been and continue to be of a serious reflection and analysis on the various stages of Western thought evolution.